2019
DOI: 10.1523/eneuro.0377-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Morphine Administration Differentially Alters Paraventricular Thalamic Neuron Activity

Abstract: The paraventricular thalamic nucleus (PVT) is a brain region involved in regulating arousal, goal-oriented behaviors, and drug seeking, all key factors playing a role in substance use disorder. Given this, we investigated the temporal effects of administering morphine, an opioid with strongly addictive properties, on PVT neuronal function in mice using acute brain slices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…The PVT has recently emerged as an important regulator of aversive motivated states and of opioid withdrawal symptoms (Zhu et al 2016). During early withdrawal from repeated morphine injections, increased synaptic strength (increased A/N ratio) is observed onto PVT neurons as well as an increase in neuronal activity (McDevitt and Graziane 2019). Early morphine withdrawal also increases synaptic strength in the PVT-NAshell projection (increased A/N ratio and increased surface expression of GluA2-lacking AMPAR).…”
Section: Paraventricular Nucleus Of the Thalamus Pathwaysmentioning
confidence: 99%
“…The PVT has recently emerged as an important regulator of aversive motivated states and of opioid withdrawal symptoms (Zhu et al 2016). During early withdrawal from repeated morphine injections, increased synaptic strength (increased A/N ratio) is observed onto PVT neurons as well as an increase in neuronal activity (McDevitt and Graziane 2019). Early morphine withdrawal also increases synaptic strength in the PVT-NAshell projection (increased A/N ratio and increased surface expression of GluA2-lacking AMPAR).…”
Section: Paraventricular Nucleus Of the Thalamus Pathwaysmentioning
confidence: 99%
“…Moreover, PVT neurons encode multiple salient features of sensory stimuli, including aversive valence ( Li et al, 2011 ; Yasoshima et al, 2007 ; Zhu et al, 2018 ). In addition, PVT neurons increase their firing rate and exhibit an increased AMPA/NMDA (2-amino-3-(3-hydroxy-5-methyl-isoxazol-4-yl)propanoic acid/N-methyl- d -aspartate) current ratio 24 h after non-contingent morphine exposure in mice ( McDevitt and Graziane, 2019 ), indicating that the PVT is recruited during early opioid withdrawal to drive aversive states ( Zhu et al, 2016 ). This is consistent with our data, showing that activation of the PVT→NAc pathway during early (24 h) withdrawal from heroin self-administration drives aversion (e.g., rtCPA) and potentiates heroin seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were singly housed for the following reasons. First, we have reliably developed morphine conditioned place preference (CPP) in singly-housed mice (Graziane et al, 2016;McDevitt and Graziane, 2019). Second, evidence suggests that socially isolated rodents are more vulnerable to developing drug-context associations (Whitaker et al, 2013).…”
Section: Animalsmentioning
confidence: 99%
“…Therefore, CPP provides a valuable tool used to understand how drugs of abuse become associated with environmental contexts, which is implicated in context-induced drug craving and relapse (O'Brien and Ternes, 1986;O'Brien et al, 1992). We have found that 5 days of morphine (10 mg/kg) conditioning elicits robust morphine CPP (Graziane et al, 2016;McDevitt and Graziane, 2019). However, it is unclear whether this ''drug contextseeking'' behavior is mediated by negative affective states.…”
Section: Introductionmentioning
confidence: 99%